FUEL PRICE INCREASE AND MANUFACTURING FIRMS SURVIVAL IN INDONESIA - Atmadji, Eko (Economic Journal of Emerging Markets, 2014)
The administered price of fuel has increased quite frequently since 1970. It has raised a concern on the survival ability of manufacturing firms that could be weakened by such policy. This research objective is for confirming whether the policy of increasing fuel price affects the survival of manufacturing firms in Indonesia. By using Instrumental Variable Probit Model, it demonstrates that increasing fuel price does not affect firms’ survival in the short-run, middle-run, as well as long-run. Nevertheless, the z-statistics increase when the period of estimation is expanded. It means that if the time span of sample observation is widened, the result might be different. Keywords: Fuel price, survival ability, instrumental variable probit model JEL classification numbers: H27, D22 Abstrak Harga bahan bakar minyak (BBM) selalu meningkat sejak 1970. Kenaikan harga ini telah menimbulkan kekhawatiran pada kemampuan kelangsungan hidup perusahaan manufaktur di Indonesia yang bisa dilemahkan oleh kebijakan tersebut. Penelitian ini dilakukan dengan tujuan mengonfirmasi apakah kebijakan kenaikan harga BBM mempengaruhi kelangsungan hidup perusahaan industri manufaktur di Indonesia. Dengan menggunakan Instrumental Variable Probit Model, hasil penelitian menunjukkan bahwa peningkatan harga BBM tidak mempengaruhi kelangsungan hidupperusahaan dalam jangka pendek, menengah, serta jangka panjang. Namun demikian, z-statistik meningkat ketika periode estimasi diperluas. Ini berarti bahwa jika rentang waktu pengamatan sampel melebar, hasilnya mungkin akan berbeda. Kata kunci: Harga BBM, kemampuan bertahan hidup, instrumental variable probit model JEL classification numbers: H27, D22